A convenient approach to the synthesis of trinucleotide phosphoramidites--synthons for the generation of oligonucleotide/peptide libraries. - Kayushin, A L (1996)
Trinucleotide phosphoramidites that correspond to the codons of all 20 amino acids were synthesized in high yield in 5g scale. Precursors of those amidites--trinucleotide phosphotriesters--have been prepared using the phosphotriester approach without protection of the 3'-hydroxyl function. The structures of trinucleotide phosphotriesters and intermediates were confirmed by 1H- and 31P-NMR spectra, mass-spectra and by analysis of SPDE-hydrolysates of deprotected preparations. Purity of the target products has been confirmed by test reactions. The synthons have been used for automated synthesis of oligonucleotides and corresponding libraries by a phosphite-triester approach. A 54mer, containing 12 randomized internal bases, and a 72mer with 24 internal randomized bases have been synthesized.